RADEC (Read-Answer-Discuss-Explain And Create): The Learning Model for Improving EFL Writing Skills in Indonesian Context - Nurnaningrum, Gayatri; Musthafa, Bachrudin; Astuti, Indri Andriani (International Conference on Elementary Education, 2025)
This study explores the RADEC (Read-Answer-Discuss-Explain-Create) learning model to improve English writing skills among Indonesian primary school students. As English is a foreign language in Indonesia, teaching English writing presents distinct challenges, including limited exposure to the language and the struggle to engage students in meaningful, motivating learning experiences. The RADEC model, designed to fit the Indonesian educational context, aims to address these challenges by promoting student engagement, critical thinking, and creativity.  The purpose of this study was to describe the RADEC learning model for improving writing skills in English learning at primary school.  Through a literature review, this study analyzes the effectiveness of RADEC in promoting critical thinking, creativity, and collaborative skills in English writing. The findings suggest that the modelâ€™s ease of use and compatibility with Indonesian educational practices make it a practical choice for primary teachers seeking innovative learning to boost writing proficiency. RADEC is not only supports English language acquisition but also prepares students with essential 21st-century skills, making it an effective framework for achieving educational objectives in Indonesia.